2017
DOI: 10.1080/02635143.2017.1353962
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of secondary pre-service teacher content knowledge (CK), pedagogical content knowledge (PCK) and attitudes regarding scientific inquiry teaching within teacher training

Abstract: Interplay of secondary pre-service teacher content knowledge (CK), pedagogical content knowledge (PCK), and attitudes regarding scientific inquiry teaching within teacher training To investigate quantitatively the longitudinal relationship between knowledge and attitudes on scientific inquiry teaching, 121 pre-service teachers for teaching biology at the secondary level in Germany and Switzerland were assessed with respect to their content knowledge (CK), pedagogical content knowledge (PCK) and attitudes on te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 81 publications
(100 reference statements)
1
9
0
2
Order By: Relevance
“…The aforementioned finding in this study is partly similar to some findings (Choi & Ramsey, 2009;DiBiase & McDonald, 2015) but differs from many findings (Houseal, Abd-El-Khalick, & Destefano, 2014;Riegle-Crumb et al, 2015;Smit et al, 2017;van Aalderen-Smeets & van der Molen, 2013Zacharia, 2003) from individualistic societies (Ajzen, 2001). In individualistic societies, teachers' science instructional intentions and behaviours are more influenced by their attitudes than societal subjective norms (Ajzen, 2001).…”
Section: Discussionsupporting
confidence: 78%
“…The aforementioned finding in this study is partly similar to some findings (Choi & Ramsey, 2009;DiBiase & McDonald, 2015) but differs from many findings (Houseal, Abd-El-Khalick, & Destefano, 2014;Riegle-Crumb et al, 2015;Smit et al, 2017;van Aalderen-Smeets & van der Molen, 2013Zacharia, 2003) from individualistic societies (Ajzen, 2001). In individualistic societies, teachers' science instructional intentions and behaviours are more influenced by their attitudes than societal subjective norms (Ajzen, 2001).…”
Section: Discussionsupporting
confidence: 78%
“…Their findings indicated that students who took the hands-on science course showed improvements in their pre-post attitude surveys, compared to participants who were not enrolled in a hands-on science course. To date, studies like that of Riegle-Crumb et al, look at changes in participant attitudes after specific interventions at a specific point in time, such as a course, or professional development (Blazar & Kraft, 2017;Smit et al, 2017). The present study looks in the other direction toward past experiences and their influence in forming existing beliefs and attitudes over time.…”
Section: Introductionmentioning
confidence: 86%
“…Students who have understood the material through the inquiry process will be able to solve physics problems. The inquiry-based learning through inquiry training models given to students in the experimental class makes them more active and develops their abilities to make learning more meaningful (Smit et al, 2017). Education can occur when students can connect between real experiences, previous knowledge, and discoveries and finally apply them (Owens & Tanner, 2017).…”
Section: C4mentioning
confidence: 99%